Ibrutinib alone or with dexamethasone for relapsed or relapsed and refractory multiple myeloma: phase 2 trial results. (13th February 2018) - Richardson, Paul G.; Bensinger, William I.; Huff, Carol Ann; Costello, Caitlin L.; Lendvai, Nikoletta; Berdeja, Jesus G.; Anderson, Larry D.; Siegel, David S.; Lebovic, Daniel; Jagannath, Sundar; Laubach, Jacob P.; Stockerl‐Goldstein, Keith E.; et al.
Summary: Novel therapies with unique new targets are needed for patients who are relapsed/refractory to current treatments for multiple myeloma. Ibrutinib is a first‐in‐class, once‐daily, oral covalent inhibitor of Bruton tyrosine kinase, which is overexpressed in the myeloma stem cell population. This study examined various doses of ibrutinib ± low‐dose dexamethasone in patients who received ≥2 prior lines of therapy, including an immunomodulatory agent. Daily ibrutinib ± weekly dexamethasone 40 mg was assessed in 4 cohorts using a Simon 2‐stage design. The primary objective was clinical benefit rate (CBR; ≥minimal response); secondary objectives included safety. Patients ( n  =   92) received a median of 4 prior regimens. Ibrutinib + dexamethasone produced the highest CBR (28%) in Cohort 4 (840 mg + dexamethasone; n  =   43), with median duration of 9·2 months (range, 3·0–14·7). Progression‐free survival was 4·6 months (range, 0·4–17·3). Grade 3–4 haematological adverse events included anaemia (16%), thrombocytopenia (11%), and neutropenia (2%); grade 3–4 non‐haematological adverse events included pneumonia (7%), syncope (3%) and urinary tract infection (3%). Ibrutinib + dexamethasone produced notable responses in this heavily pre‐treated population. The encouraging efficacy, coupled with the favourable safety and tolerability profile of ibrutinib, supports its further evaluation as part of combination treatment.